Structural Risk Assessment and Mitigation for Low- to Mid-Rise Residential Buildings in China - Korkmaz, Kasim A. (Frontiers in Built Environment, 2017)
China has experienced major earthquakes recently. The 2014 Ludian earthquake struck Ludian County, Yunnan, (Mw= 6.1) on 3 August, 2014. On April 20, 2013, Ya'an earthquake (Mw=6.9), on April 14th 2010, Qinghai earthquake (Mw = 7.1), on July 9th 2009, Yunnan earthquake (Mw = 6.0), and on May 12th 2008 Sichuan earthquake (Mw = 7.9) struck China. Among these disasters, the most devastating, the Sichuan earthquake, resulted in the collapse of 5 million buildings and damage to more than 21 million. Human loss was also high with over 60,000 people dead, 360,000 injured and more than 14 million people displaced. South-west China lies in an area that is prone to earthquakes. In 1970, a magnitude 7.7 earthquake in Yunnan with 15,000 lost. This study presents a detailed risk assessment for a structural risk assessment and mitigation for low to mid-rise residential buildings for China. The risk assessment, through seismic hazard assessment approaches, evaluates the impact of the disasters for integrated structural health monitoring. Among the results of the investigation, relations and links between safety and risk are defined.